1993
DOI: 10.1177/030006059302100602
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Controlled Double-Blind Study of the Hypnotic Effects of Zolpidem in Patients with Chronic ‘Learned’ Insomnia: Psychometric and Polysomnographic Evaluation

Abstract: In a pilot double-blind trial in 21 patients with learned or idiopathic insomnia (DSM-IIIR), patients received placebo for 1 week (nights 1-7), either active (zolpidem, 10 mg) or placebo treatment for 2 weeks (nights 8-21) and then placebo for a further week (nights 22-28). Variables to measure efficacy, rebound and withdrawal were assessed daily from day 1 to day 28. Polysomnographic recordings together with sleep cycle analysis were performed on nights 7, 21 and 28. Patients treated with 10 mg zolpidem for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…In addition, one paper evaluated the effectiveness of zolpidem extended release 6.25 mg 80 and one paper assessed zolpidem extended release 12.5 mg. 81 Five studies examined the effects of zolidem 10 mg on objective sleep latency. 60,73,76,77,82 The mean reduction (vs. placebo) for PSG-determined latency to sleep exceeded the threshold for clinical significance. Ten studies presented patient-reported sleep latency data.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In addition, one paper evaluated the effectiveness of zolpidem extended release 6.25 mg 80 and one paper assessed zolpidem extended release 12.5 mg. 81 Five studies examined the effects of zolidem 10 mg on objective sleep latency. 60,73,76,77,82 The mean reduction (vs. placebo) for PSG-determined latency to sleep exceeded the threshold for clinical significance. Ten studies presented patient-reported sleep latency data.…”
Section: Discussionmentioning
confidence: 95%
“…57,59,60,70,[72][73][74][75][76][77][78][79] The overall quality of evidence was downgraded to very low due to significant heterogeneity, imprecision, and risk of publication bias. The evidence for zolpidem 10 mg was weakly in favor of its effectiveness for improving sleep onset, sleep maintenance, sleep quality, SE and TST.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Zolpidem has a rapid onset of action and does not negatively affect physiological 254 sleep architecture.!? - 12 It has been observed that cessation of zolpidem treatment does not induce significant rebound insomnia or withdrawal manifestations.w-> It is not known whether treatment of insomnia with a non-benzodiazepine such as zolpidem induces a more natural sleep in patients with chronic insomnia, after the cessation of long-term use of benzodiazepines. Discontinuation of longterm benzodiazepines can be difficult owing to rebound and/or withdrawal symptoms, which leads to chronic use and dependency in some patients."…”
Section: Introductionmentioning
confidence: 99%